Characterization of patients treated with conventional dermatological surgery at hospital level - Hernández López, Aimet; Vega Jiménez, Junior; Naranjo del Pino, Daniel; López González, Humberto Alexis; Gonzalez Gonzalez, Lisneybi (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: In recent decades the incidence of skin lesions that affect the patient's health has been increasing and the dermatosurgical field has boomed.Objective: To characterize patients treated with conventional dermatological surgery at the hospital level.Methods: An observational, descriptive and cross-sectional study was carried out on patients undergoing dermatological surgery treated in a dermatology consultation at the Faustino Pérez Hernández provincial clinical surgical teaching hospital in the province of Matanzas, Cuba, between September 2020 and September 2021. The sample consisted of 35 cases. The research was carried out in the Dermatology service during four moments (outpatient consultation, surgical procedure, post-surgical re-consultation and re-consultation).Results: The female sex and the sixth decade of life predominated with 62,8 % each. Skin phototype I represented 40 %. Basal cell carcinoma was identified as the predominant clinical diagnosis in 40 %. Elliptical excision with 45,7 % was the most practiced surgical technique. Wound dehiscence with 54,5 % was the most frequent complication of the surgical procedure.Conclusions: The study demonstrated the safety and efficiency of dermatological surgery and the strengthening of the foundations of the specialty as a surgical clinic.